Finite element spine models and spinal instruments: A review - Akıncı, Saliha Zeyneb; Arslan, Yunus Ziya (World Scientific Publishing Co Pte Ltd, 2022)
There is considerable biomechanics literature on finite element modeling and analysis of the spine. To accurately mimic the biomechanical behavior of the vertebral column, a generated computational model has to include anatomical structures that are consistent with physiological reality. In this review article, we focused on the finite element spine models that have been developed by various approaches in the literature. Firstly, the anatomical features of the spine and the spinal components have been briefly explained. We then focused on the modeling stages of vertebrae, ligaments, facet joints, intervertebral discs, and spinal instruments. With this paper, we expect to provide a comprehensive resource regarding the modeling preferences used in spine modeling.
Keywords: Biomechanical Behavior; Finite Element Method; Reconstruction of Imaging Data; Spine Models